Reservoir operation-induced hydrodynamic disturbances affect the distributions of Cd, Cu, and Pb in the riparian soil of the water-level-fluctuation zone - Zhang, Wei; Sun, Honglei; Liang, Yun; Tang, Xiangyu; Fang, Yuxiao; Cui, Junfang; Wang, Xingmin; Zhou, Qigang (Journal of soils and sediments, 2021)
Purpose This study aimed to relate the altitudinal and vertical distributions and occurrences of major heavy metals (HMs) to soil physicochemical properties in the riparian soils subject to periodic and intense wet–dry cycles Materials and methods Cadmium (Cd), copper (Cu), and lead (Pb) and their chemical fractions were investigated in the riparian soil (0–40 cm) of the upland and within the water-level-fluctuation zone (WLFZ) at two tributary backwaters of the Three Gorges Reservoir (TGR) in China. Selected soil basic properties and pore structures determining the distribution of HMs and their fractions were identified using correlation and redundancy analysis Results and discussions Cd showed moderate–strong contamination and prevailed in non-residual fraction (>73.2%) in the riparian soil of the tributary backwaters in the TGR. In contrast, Cu and Pb exhibited slight contamination and prevailing in residual fraction (>50.3%). Enrichment of HMs in the lower end relatively flat WLFZ where flow rate decreased abruptly and dramatically was observed. Cd exhibited the largest coefficient of variation (CV, up to 0.263) across soil profiles while Cu showed a relatively homogeneous profile distribution in the riparian soil. Soil organic matter (SOM), cation exchange capacity (CEC), and pH were identified to be the primary factors determining the distributions of Cd, Cu, Pb, and their chemical fractions, respectively, in the riparian soil with a high macroporosity. Nevertheless, soil porosity was the dominant factor (>65.0%) determining the distributions of all the three HMs and their fractions in the non-drainable micropore-dominated riparian soil Conclusions Soil basic property and pore structure variations due to periodic hydrodynamic disturbances from reservoir operation are closely related to the redistribution of HMs in the riparian soil. The coupling of these two variations is strongly suggested to assist reliable evaluation of various contaminants, including but not limited to HMs, regarding their spatial redistributions and mobilization potentials in the vadose zone at larger scales in response to climate change.